DETERMINAN KEPUTUSAN PETANI TERHADAP KONVERSI LAHAN SAWAH MENJADI PERMUKIMAN - Umiyati Kulsum; Bustanul Arifin; Zainal Abidin (Lampung University, 2015)
The objectives of this research are to analyze the factors that influence farmer’s decisions in whether or not maintaining rice-fields, to estimate the projection of rice-fields area and production of rice in year 2022, and to produce comparative analysis of land rent between rice-fields and housing. The research was conducted in the villages of Linduk in Pontang Sub-district of Serang Districts in the Province of Banten and Tajimalela in Kalianda Sub-distrtict of South Lampung District in the Province of Lampung. Data collection was performed in April to May of 2013, using a quota sampling method. The number of samples as much as 120 respondents, consisting of 60 farmers maintaining their rice-fields and 60 farmers not maintaining their rice-fields. Econometrics analysis with binary logistic regression and linier regression was used in this research. The results showed that factors that influenced the decisions of farmers in maintaining rice-fields was land tax, land prices, household income, rice-fields area, and land status, while the research sites was not significant variable. Projection of rice-fields area and production of rice in 2022 was estimated to reach 38,702 hectares and 299,238 tons respectively in Serang Disctrict, and 32,067 hectares and 351,975 tons respectively in South Lampung District. Land rent comparison between rice-fields and housing was 1 to 1.47 in Serang Districts and 1 to 5.59 in South Lampung District. The study recommends policy consistency in spatial planning and better law enforcement to prevent further conversion of rice-fields in both districts and in Indonesia as a whole. Key words: land rent, projection of rice production, rice-fields convertion